The Effect of Early Mobilization on Improved Motor Function in Patients with Non-Hemorrhagic Stroke in the Neurology Ward of Jenderal Ahmad Yani General Hospital, Metro City - Diah Nur Isnaini; M. Farhan Al Farisi (INDOGENIUS, 2026)
Background & Objective: A stroke is a disruption of brain function caused by a blockage in blood flow to the brain (non-hemorrhagic stroke), resulting in tissue damage and impaired motor function. One effective nursing intervention to accelerate the recovery of motor function is early mobilization, which involves gradually moving the patient once their hemodynamic condition has stabilized. Early mobilization has been shown to prevent complications of immobility, increase muscle strength, and improve body movement coordination in stroke patients. This study aims to determine the effect of early mobilization on improving motor function in non-hemorrhagic stroke patients in the Neurology Ward of Jenderal Ahmad Yani General Hospital, Metro City. Method: This study is a pre-experimental study using a one-group pre-test post-test design. The sample consisted of 58 respondents selected using purposive sampling. Data collection was conducted using a motor function observation sheet before and after early mobilization. Data analysis utilized the Wilcoxon Signed-Rank Test. Result: The results indicated that prior to early mobilization, the majority of respondents (51 respondents, 87.9%) had moderate motor function, whereas after early mobilization, the majority (41 respondents, 70.7%) remained in the moderate category, with improved movement ability in the extremities. The Wilcoxon test yielded a p-value of 0.000 (< 0.05), indicating a significant effect of early mobilization on the improvement of motor function in non-hemorrhagic stroke patients. Conclusion: There is a significant association between early mobilization and improved motor function in non-hemorrhagic stroke patients in the Neurology Ward of General Ahmad Yani Regional General Hospital, Metro City. Early mobilization has been proven to help accelerate the rehabilitation process and improve patients’ mobility. It is recommended that nursing staff routinely perform early mobilization according to the patient’s condition as part of standard care for stroke patients.